Comparison of Hemodynamic Stress Response of Intravenous Lidocaine Versus Magnesium Sulphate after Endotracheal Intubation - Tanveer, Mah Rukh; Ahmad, Danyal; Fayyaz, Muhammad Aatir; Mohyudin, Ammara; Ahsan, Hafiz Muhammad; Bandesha, Yousaf (Biological and Clinical Sciences Research Journal, 2025)
Endotracheal intubation induces a marked hemodynamic stress response, characterised by increases in heart rate (HR), blood pressure (BP), and mean arterial pressure (MAP), which can predispose patients, particularly those with cardiovascular comorbidities, to adverse events. Intravenous lidocaine and magnesium sulphate are pharmacologic agents used to attenuate this response, yet their comparative efficacy in the Pakistani surgical population remains underexplored. Objective: To compare the effects of intravenous lidocaine and magnesium sulphate on hemodynamic responses following endotracheal intubation in patients undergoing elective general surgery. Methods: A randomized controlled trial was conducted at the Department of Anesthesiology, Ibn-e-Siena Hospital and Research Institute, Multan, Pakistan, from January 2024 to July 2024. Sixty ASA I–II patients aged 20–60 years were randomly assigned to receive either lidocaine 1.5 mg/kg (Group L) or magnesium sulphate 40 mg/kg (Group M) intravenously, 90 seconds before induction. Hemodynamic parameters (HR, systolic BP, diastolic BP, MAP) were recorded at baseline, immediately before intubation, and at 1, 3, and 5 minutes post-intubation. The primary outcome was MAP at 5 minutes post-intubation. Data were analysed using independent-samples t-tests and chi-square tests, with p < 0.05 considered significant. Results: Baseline demographics and pre-intubation hemodynamic parameters were comparable between groups (p ≥ 0.05). At 5 minutes post-intubation, MAP was significantly higher in Group L compared to Group M (92.8 ± 7.6 vs. 87.9 ± 7.3 mmHg; p = 0.014). Group M showed greater reductions from baseline in MAP (−5.0 ± 5.1 vs. −0.6 ± 5.2 mmHg; p = 0.001), systolic BP (−8.1 ± 6.0 vs. −0.3 ± 6.5 mmHg; p < 0.001), and diastolic BP (−4.8 ± 5.1 vs. −1.4 ± 5.4 mmHg; p = 0.008). The increase in HR was smaller in Group M (+1.1 ± 4.1 bpm) compared to Group L (+3.3 ± 4.4 bpm; p = 0.025). Post-stratification analysis confirmed the MAP advantage of magnesium across all age, gender, ASA class, and BMI subgroups. Conclusion: Both lidocaine and magnesium sulphate effectively attenuate the hemodynamic stress response to endotracheal intubation. Lidocaine maintained higher post-intubation MAP, while magnesium resulted in greater reductions in BP and HR, with consistent effects across subgroups. Magnesium sulphate may be preferred in patients where lower post-intubation pressures are desirable, while lidocaine may benefit those requiring more stable MAP maintenance.